Knowing Personality Traits on Facebook Status Using the NaÃ¯ve Bayes Classifier - Sarwani, Mohammad Zoqi; Salafudin, Muhammad Shubkhan; Sani, Dian Ahkam (International Journal of Artificial Intelligence & Robotics (IJAIR), 2020)
With the development of social media trends among students by using Facebook social media, students can communicate and pour out everything that is felt in the form of status. Personality is the character or various characters of a person - therefore, how a person to adjust to the surrounding environment for the achievement of communication smoothly. In the personality category, many things classify a person's category in the psychologist theory. In this exercise, the Big Five, the psychologist theory, is described in five codes, namely Openness, Conscientiousness, Extraversion, Agreeables, Neuroticism. Naive Bayes Classifier is used to determine the highest probability value with the aim to determine the highest value. The data used are two namely training data and testing data obtained from the Facebook status of students. From the data obtained can be tested in the system that the accuracy value is 88%.